Pengaruh Literasi Pajak, Sosialisasi Perpajakan, dan Pemanfaatan Financial Technology Terhadap Kepatuhan Wajib Pajak Dimana Digitalisasi Perpajakan Sebagai Variabel Moderasi - Nur Atifa; Afifudin Afifudin; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Based on KUP Law Number 28 of 2007 Article 1 paragraph 1, the definition of tax is a mandatory contribution to the state owed by an individual or entity that is coercive based on the Law, with no direct compensation and used for state purposes for the greatest prosperity of the people. In 2020 Indonesia's tax ratio experienced a decline that fell considerably, this year is where Indonesia's tax ratio declined the most due to the Covid-19 pandemic which limited public activities. This shows an indication that the level of awareness and compliance of the Indonesian people on taxes still tends to be low The purpose of this study is to determine the effect of tax literacy variables, tax socialization, and the use of financial technology on taxpayer compliance. The research location in this study is the Islamic University of Malang. This type of research is quantitative research. This research was conducted from December 2022 to June 2023. The number of samples was 88 respondents. data analyzed with SPSS 26.The results of this study show that tax literacy and tax socialization affect taxpayer compliance, while the use of financial technology does not affect taxpayer compliance. Tax digitalization can moderate tax literacy and tax socialization. However, digitalization cannot moderate the use of financial technology. Further researchers are expected to use other independent variables to increase the variety of research and find out other causes that can affect taxpayer compliance. For the Director General of Taxes, it is expected to utilize financial technology in the world of taxation to make it easier for taxpayers.Keywords: Tax compliance, tax digitalization, tax literacy, tax socialization, financial technology utilization.